2022
DOI: 10.3233/bmr-200342
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two periods of Schroth exercises for improving postural stability indices and Cobb angle in adolescent idiopathic scoliosis

Abstract: BACKGROUND: Adolescents with idiopathic scoliosis present postural instability when compared with healthy subjects. Although Schroth exercises therapy (SET) is broadly utilized, its effect on postural stability is still not clear. OBJECTIVES: To compare the two treatment periods of the SET for improving the postural stability indices and Cobb angle, and to examine the correlation between the Cobb angle and stability indices in adolescent idiopathic scoliosis (AIS). METHODS: Twenty girls aged 10–16 years with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Radwan, Ibrahim, and Mahmoud also demonstrated the effects of Schroth's exercise for three months on OSI, APSI, and MLSI in patients with AIS [2]. The OSI decreased significantly with each measurement (baseline, one-month and three-months post-intervention).…”
Section: Hippotherapy and Schroth's Exercisementioning
confidence: 85%
See 4 more Smart Citations
“…Radwan, Ibrahim, and Mahmoud also demonstrated the effects of Schroth's exercise for three months on OSI, APSI, and MLSI in patients with AIS [2]. The OSI decreased significantly with each measurement (baseline, one-month and three-months post-intervention).…”
Section: Hippotherapy and Schroth's Exercisementioning
confidence: 85%
“…Exercise approaches have also been used to improve postural balance and stability in AIS patients. A previous study by Radwan et al demonstrated that scoliosis exercise improved postural stability and Cobb angle in the AIS group compared with the control group [2]. AIS patients who are known to have a posteriorly shifted COP position on the sagittal plane, also have a greater postural instability than typically developed adolescents [30].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations